Non-albicans Candida Infection: An Emerging Threat. (22nd October 2014) - Deorukhkar, Sachin C.; Saini, Santosh; Mathew, Stephen
Abstract : The very nature of infectious diseases has undergone profound changes in the past few decades. Fungi once considered as nonpathogenic or less virulent are now recognized as a primary cause of morbidity and mortality in immunocompromised and severely ill patients. Candida spp. are among the most common fungal pathogens. Candida albicans was the predominant cause of candidiasis. However, a shift toward non- albicans Candida species has been recently observed. These non- albicans Candida species demonstrate reduced susceptibility to commonly used antifungal drugs. In the present study, we investigated the prevalence of non- albicans Candida spp. among Candida isolates from various clinical specimens and analysed their virulence factors and antifungal susceptibility profile. A total of 523 Candida spp. were isolated from various clinical specimens. Non- albicans Candida species were the predominant pathogens isolated. Non- albicans Candida species also demonstrated the production of virulence factors once attributed to Candida albicans . Non- albicans Candida demonstrated high resistance to azole group of antifungal agents. Therefore, it can be concluded that non- albicans Candida species have emerged as an important cause of infections. Their isolation from clinical specimen can no longer be ignored as a nonpathogenic isolate nor can it be dismissed as a contaminant.